2015
DOI: 10.3889/oamjms.2015.123
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines Vaspin and Visfatin in Obese Children

Abstract: BACKGROUND:Adipokines provides new insights about the physiology, pathology and treatment of obesity.AIM:We investigated the association between serum vaspin and serum visfatin concentrations with obesity in Egyptian children.MATERIAL AND METHODS:Twenty two obese children with body mass index (BMI) above 95th percentile; 11 males and 11 females were included in this study. Their mean age was 9.18 ± 2.8 years. After general clinical examination, fasting blood glucose, triglycerides, total cholesterol and high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
(22 reference statements)
1
10
1
3
Order By: Relevance
“…Additionally, the serum vaspin concentration in obese patients was higher than that in nonobese patients in the same research [ 17 ]. Salama et al (2015) found that vaspin levels are increased in obese children and identified correlations between vaspin concentration and WHR; however, they concluded that vaspin was a less sensitive indicator of abdominal obesity and insulin resistance in obese children compared with visfatin [ 20 ]. Cekmez et al reported that large for gestational age children had a higher vaspin concentration than those who were appropriately sized for gestational age [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the serum vaspin concentration in obese patients was higher than that in nonobese patients in the same research [ 17 ]. Salama et al (2015) found that vaspin levels are increased in obese children and identified correlations between vaspin concentration and WHR; however, they concluded that vaspin was a less sensitive indicator of abdominal obesity and insulin resistance in obese children compared with visfatin [ 20 ]. Cekmez et al reported that large for gestational age children had a higher vaspin concentration than those who were appropriately sized for gestational age [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these well-studied adipocytokines, a large number of additional adipokines emerged during the last years, including adipocyte-fatty acid-binding protein (A-FABP), retinol binding protein 4 (RBP4), lipocalin-2, omentin-1, and vaspin [48, 58, 64] (Table 2). Some of these may be promising biomarkers in the context of metabolic disturbances.…”
Section: The Role Of Adipocytokines In the Pathogenesis Of Metabolic mentioning
confidence: 99%
“…NAMPT is significantly associated with several anthropometric parameters (BMI, waist circumference, and hip circumference) [64], components of MetS, and inflammation [48] in children. While Kotnik et al [48] found no association between NAMPT and insulin resistance, Salama et al [64] dem­onstrated a significant link between NAMPT and an impaired homeostatic model assessment for insulin resistance (HOMA-IR).…”
Section: The Role Of Adipocytokines In the Pathogenesis Of Metabolic mentioning
confidence: 99%
“…The serum vaspin levels were decreased in CF children like in ischemic heart disease and girlswith anorexia nervosa [30][31][32]. Decreased serum vaspin concentrations may simply reflect reduced fat mass in CF like in obese subjects after 12-weeks short term weight reduction program [33].…”
Section: Discussionmentioning
confidence: 97%